Concrete Structures in Earthquake - Hsu, Thomas T. C.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book gathers 23 papers by top experts from 11 countries, presented at the 3rd Houston International Forum: Concrete Structures in Earthquake. Designing infrastructures to resist earthquakes has always been the focus and mission of scientists and engineers located in tectonically active regions, especially around the "Pacific Rim of Fire" including China, Japan, and the USA. The pace of research and innovation has accelerated in the past three decades, reflecting the need to mitigate the risk of severe damage to interconnected infrastructures, and to facilitate the incorporation of high-speed computers and the internet. The respective papers focus on the design and analysis of concrete structures subjected to earthquakes, advance the state of knowledge in disaster mitigation, and address the safety of infrastructures in general.
Behavior Prediction of Reinforced Concrete Members in Earthquake -- Experimental Study of Novel Rc Frames Considering Earthquake and Progressive Collapse -- Research on Resilient Reinforced Concrete Building Structural System -- Recent Advances on Seismic Retrofit of Reinforced Concrete Shear Walls with Frp -- Assessment of the Boundary Regions Stability of Special Rc Walls -- Essential Requirements for Reinforced Concrete Structures of Limited Area and Height -- Issues Related to the Rapid Seismic Repair of Concrete Bridge Columns -- Test and Analysis of a Self-Centering Concrete Frame under Seismic Action.
Keywords: Fire prevention; Buildings -- Protection; Building materials; Buildings -- Design and construction; Light construction; Steel construction; Lightweight construction; Mechanics, Applied; Solids; Fire Science, Hazard Control, Building Safety; Building Materials; Building Construction and Design; Light-weight Construction, Steel and Timber Construction; Solid Mechanics